2018
DOI: 10.19105/ojbs.v12i2.1930
|View full text |Cite
|
Sign up to set email alerts
|

Speech Errors Produced by EFL Learners of Islamic Boarding School in Telling English Story

Abstract: The students of Islamic Boarding School Nurul Islam are used to learn spoken English, but they still make some errors when they are speaking. They often produce some speech errors when they are making an English conversation or when they are getting turn to speak in front of the class. This study aims to investigate the existence and the frequency of speech errors especially Silent Pause and Filled Pause produced by the students of Islamic Boarding School Nurul Islam in telling English Story. This research is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Kafifah and Aini (2020) also found the same findings in their research that the Silent Pause contributed most to the total number of errors made by the respondents. The finding on the number of error speech in the form of Silent Pause and Filled Pause is also the same as what Utami andMalihah (2018, p. 1991) found in her study that among 603 pausing speech errors, the Silent Pause appeared 524 times or contributed to the whole error speech number while the rest was Filled Paused which appeared 79 times or 13% of the total. Another study conducted by Firdausi (2016) showed that the most error found was also the Silent Pause in which it contributed as many as 44.27% to the total number of errors.…”
Section: Discussionsupporting
confidence: 86%
“…Kafifah and Aini (2020) also found the same findings in their research that the Silent Pause contributed most to the total number of errors made by the respondents. The finding on the number of error speech in the form of Silent Pause and Filled Pause is also the same as what Utami andMalihah (2018, p. 1991) found in her study that among 603 pausing speech errors, the Silent Pause appeared 524 times or contributed to the whole error speech number while the rest was Filled Paused which appeared 79 times or 13% of the total. Another study conducted by Firdausi (2016) showed that the most error found was also the Silent Pause in which it contributed as many as 44.27% to the total number of errors.…”
Section: Discussionsupporting
confidence: 86%
“…Sometimes speakers make errors during the execution process of speech, and it can interfere with the effectiveness of the communication process, the error in speaking is referred as speech errors. Speech errors (some says slip of tongue) are unintentional mistakes made by a speaker from the target form intends to produce, it is general errors in speaking that can happen to anyone during verbal communication (Tampubolon & Lubis, 2021;Utami & Malihah, 2018;Vahlevi et al, 2020;Yahya, 2022;Zhu & Liu, 2018). To conclude, speech errors is regarded as a discrepancy between what the speakers want to convey with what they actually said.…”
Section: The Background Of the Studymentioning
confidence: 99%
“…Many scholars conducted the study of speech errors in some field such as in students' utterances in speaking English (Irmayana et al, 2020;Kafifah & Aini, 2020;Pravitasari, 2017;Utami & Malihah, 2018), lexical erros in Mandarin (Wan & Allassonnière-Tang, 2021), speech error in L2 (Pepito, 2019), speech error in Female singer (Harastasya et al, 2020), Indonesian daily conversation (Lapasau & Setiawati, 2021;Syukri, 2018), South Korean TV shows (Tampubolon & Lubis, 2021;Yahya, 2022), phonological speech error (Frisch & Wright, 2002), morphological speech error (Sadapotto et al, 2021), and movie (Mutmainnah, 2014;Vahlevi et al, 2020). Researcher analyzed BO and DT speech in "60 Minutes" used nine types of speech errors proposed by Clark & Clark (1977), there are nine types of errors namely: silent Pause, filled pause, repeats, retraced false start, unretraced false start, correction, stutter, interjection and slip of tongue.…”
Section: The Background Of the Studymentioning
confidence: 99%